ITIL® 4 : High-velocity IT : reference and study guide (TSO (The Stationery Office), 2022)
The ITIL 4 High-velocity IT (HVIT) reference and revision guide is one of five ITIL 4 revision aids published by TSO, following on from ITIL 4 Foundation revision guide. Digital technology is becoming increasingly important. This title focuses on digital products and services, including digital customer experiences, covering good organizational practices and mental models all from a practitioner’s perspective. Use of working practices such as Agile and Lean, and technologies such as Cloud and Automation are included. This pocket guide is an aid for revision and preparation for taking the ITIL 4 Managing Professional: HVIT certification, and post-certification it is a quick useful reference. It summarizes key topics for exam preparation, includes key figures from the core guidance, provides an examination overview, tips for taking the exam and a summary table linking learning outcomes to references in the text and to core guidance.